Digital Transformation Model for Strengthening Brand Equity and Competitiveness of Printing MSMEs - Linda Norhan; Umi Narimawati; Bobi Kurniawan (Eduvest - Journal of Universal Studies, 2026)
The rapid advancement of digital technology has transformed the business environment and compelled Micro, Small, and Medium Enterprises (MSMEs) to adopt digital strategies to maintain competitiveness. In the printing industry, many MSMEs still rely on conventional business processes despite having limited digital presence, resulting in suboptimal customer engagement and brand development. This study aims to develop and validate a digital transformation model that strengthens brand equity and competitiveness through website quality in printing MSMEs. A sequential mixed-method approach was employed, consisting of website system development and quantitative evaluation. Data were collected from 100 customers of Buana Jaya Printing who had interacted with the newly developed digital platform. Respondents were selected using purposive sampling, and the data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) with SmartPLS 4.0. The findings reveal that digital transformation has a significant positive effect on website quality and brand equity. Website quality also significantly enhances brand equity by improving user experience, trust, and customer satisfaction. Furthermore, brand equity was found to positively influence competitiveness, indicating that stronger brand value contributes to sustainable market advantage. The mediation analysis confirms that website quality serves as an important mechanism through which digital transformation strengthens brand equity. In conclusion, digital transformation supported by high-quality websites can significantly improve brand equity and competitiveness, providing a strategic pathway for printing MSMEs to achieve sustainable growth in the digital era.